High‐pressure studies of palladium and platinum thioether macrocyclic dihalide complexes. Issue 3 (1st June 2014) - Allan, David R.; Bailey, Daniel; Bird, Nigel; Blake, Alexander J.; Champness, Neil R.; Huang, Deguang; Keane, Conal P.; McMaster, Jonathan; Prior, Timothy J.; Tidey, Jeremiah P.; Schröder, Martin
<x xml:space="preserve">Abstract</x> The mononuclear macrocyclic PdII complex cis‐[PdCl2([9]aneS3)] ([9]aneS3 = 1, 4, 7‐trithiacyclo‐nonane) converts at 44 kbar into an intensely coloured chain polymer exhibiting distorted octahedral coordination at the metal centre and an unprecedented [1233] conformation for the thioether ligand. The evolution of an intramolecular axial sulfur–metal interaction and an intermolecular equatorial sulfur–metal interaction is central to these changes. High‐pressure crystallographic experiments have also been undertaken on the related complexes [PtCl2([9]aneS3)], [PdBr2([9]aneS3)], [PtBr2([9]aneS3)], [PdI2([9]aneS3)] and [PtI2([9]aneS3)] in order to establish the effects of changing the halide ligands and the metal centre on the behaviour of these complexes under pressure. While all complexes undergo contraction of the various interaction distances with increasing pressure, only [PdCl2([9]aneS3)] undergoes a phase change. Pressure‐induced I...I interactions were observed for [PdI2([9]aneS3)] and [PtI2([9]aneS3)] at 19 kbar, but the corresponding Br...Br interactions in [PdBr2([9]aneS3)] and [PtBr2([9]aneS3)] only become significant at much higher pressure (58 kbar). Accompanying density functional theory (DFT) calculations have yielded interaction energies and bond orders for the sulfur–metal interactions.